Variations in trace elements, isotopes, and organic geochemistry during the Hangenberg Crisis, Devonian–Carboniferous transition, northeastern Vietnam. (11th February 2020) - Shizuya, Atena; Oba, Masahiro; Ando, Takuto; Ogata, Yukari; Takashima, Reishi; Nishi, Hiroshi; Komatsu, Toshifumi; Nguyen, Phong D.
Abstract: The Hangenberg Crisis at the Devonian–Carboniferous boundary is known as a polyphase extinction event that affected more than 45 % of marine and terrestrial genera. As the cause of this event is still debated, analyses were carried out on sedimentary samples from the Devonian–Carboniferous Pho Han Formation in northeastern Vietnam to reconstruct the paleoenvironment around the time of this event using stable carbon isotopes; total sulfur; manganese; vanadium; molybdenum; and sedimentary organic matter, such as dibenzothiophenes, cadalene, and regular steranes. These geochemical signatures provide a high‐resolution redox history for this section and show that transgression‐driven high primary productivity, possibly enhanced by terrestrial input, caused severe oxygen depletion along the continental margin of the South China block during the Hangenberg Crisis. Abstract : Multi‐proxy analyses were carried out on Devonian¬–Carboniferous sediments from the Pho Han Formation, northeastern Vietnam to reconstruct the paleoenvironment around the time of the Hangenberg Crisis. The geochemical signatures provide a high‐resolution redox history for this section and show that transgression‐driven high primary productivity possibly enhanced by terrestrial input caused severe oxygen depletion along the continental margin of South China block during the event.